Diffusion Tensor Imaging Abnormalities in the Cerebellum of Children with ADHD and Epilepsy/ADHD - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2009)
Diffusion tensor imaging was used to investigate cerebellar structure in children with combined epilepsy/ADHD and ADHD alone, at the University of Basel, Switzerland.